Persulfate-assisted anaerobic digestion systems: advances in microbial electron transport chain reconstruction and metabolic regulation driven by reactive oxygen species - Yingjin Song; Sheng Xu; Yanshan Wang; Lan Mu; Huiling Niu; Qingyi Li; Yinjie Zhong; Yvxing Luo; Zhi Wang; Beibei Yan; Guanyi Chen (Bioresource Technology, 2026)

New insights into the temporal speciation of phosphorus during anaerobic digestion of wetland biomass wastes - Fan Yu; Junxia Wang; Zhi Wang; Lan Mu; Xutong Wang; Qianqian Guo; Xiaoqiang Cui; Yanjun Hu; Beibei Yan; Guanyi Chen (Bioresource Technology, 2026)

Unveiling the pathogenesis and therapeutic strategies of Alzheimer’s disease through cuproptosis - Shuangfeng Xu; Jing Mu; Zhifeng Wang; Jiao Yang; Daman Tian; Ting Shi; Junfeng Lan; Pengfen He; Zhihui Hao; Youchuan Fu; Liwei Xing; Jianzhou Ye; et al. (BioMetals, 2026)

Photoperiod induces alterations in redox homeostasis, immune response, and responses to light stimulation in the red swamp crayfish (Procambarus clarkii) - Lang Zhang; Qi Bai; Yingchun Mu; Yali Yu; Liting Ye; Lu Qiao; Wenya Ji; Jie Peng; Meiping Lan; Ziwei Song; Yu Fang (Aquaculture, 2026)

METTL18-catalyzed histidine methylation of YTHDF2 promotes mRNA stability - Wen-Lan Yang; Meng-Xia Liu; Yue Han; Xing-Xing Li; Ye Gu; Xinyuan Tian; Mengqian Mu; Xiaolin Zhang; Yanzhe Wang; Xinyu Li; Yu-Sheng Chen; Chun-Chun Gao; et al. (Science China Life Sciences, 2026)

Nitrogen fertilization drives bacterial turnover versus fungal persistence for straw-derived C and N stabilization in a wheat-maize rotation - Guocui Ren; Xiuli Xin; Haowei Ni; Xianfeng Zhang; Lan Mu; Wenliang Yang; Shuchun Ge; Shaopu Pang; Anning Zhu (Soil and Tillage Research, 2026)

Nitric acid-modified co-pyrolyzed biochar from gentamicin mycelial residue and biomass regulates cattle manure composting: Reducing carbon loss and enhancing humification - Yingjin Song; Huiling Niu; Yamei Zeng; Guanyi Chen; Zeng Dan; Beibei Yan; Lan Mu; Yuxing Luo; Yinjie Zhong; Sheng Xu; Qingyi Li; Anna Jin (Journal of Environmental Management, 2026)

ROS regulate pollen germination and tube growth in Betula platyphylla with involvement of H2O2 and polyamine oxidase BpPAO2 - Chaoning Zhao; Wendi Mu; Jiaqi Shi; Jiayuan Shi; Bello Hassan Jakada; Gege Dou; Taihe Zhao; Huiyi Xie; Siyu Dong; Ying Wu; Xingguo Lan (Physiology and Molecular Biology of Plants, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

Age, source, and formation mechanism of Cryogenian cap Mn‑carbonates in South China - Zhongwu Lan; Nick M.W. Roberts; Sandra Kamo; Xiaodie Mu; Qi Zhou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Predicting pedestrian routing variability among web-based platforms: A machine learning framework for accessibility research - Mohammed Almusidi; Lan Mu (Journal of Transport Geography, 2026)

From intention to action under institutional nudges: governmental pathways to climate adaptation technology adoption in rural China - Lan Mu; Ying Li; Haoying Liu; Qiongyao Wang; Meimei Wang (Journal of Rural Studies, 2026)

Coupled influence of Western Pacific moisture anomalies and mid-tropospheric humidity on October precipitation in Yunnan Province Southwest China - Wen-Jun Sun; Zhen-Peng Tao; Zi-Yang Zhang; Tian-Qing Lan; Taohui Li; Peng Zi; Jian Zhang; Yao Wu; Ming-Qiang Liang; Chao-Jun Chen; Yuan-Yuan Mu; Jun-Yun Li; et al. (Atmospheric Research, 2026)

Cold Stress and Molecular Adaptations in Aquatic Organisms: A Comparative Review of Fish, Crustaceans, and Mollusks - Lan Li; Yihong Mu; Chunrong Zuo; Minfang Zhao; Zhiqiu Huang; Wenli Zhang; Meihong Qiu; Yi Huang (Fishes, 2026)
Cold stress poses a significant challenge to aquatic organisms, affecting their survival, growth, and metabolic processes. This review explores the molecular mechanisms by which fish, crustaceans, and mollusks respond to cold stress, highlighting the shared and species-specific pathways that facilitate adaptation. Common responses to cold stress include modulation of energy metabolism, regulation of oxidative stress, immune responses, and maintenance of proteostasis. In particular, the activation of the adenosine 5′-monophosphate-activated protein kinase (AMPK) and mechanistic target of rapamycin (mTOR) pathways plays a critical role in regulating energy balance and autophagy in response to low temperatures. Furthermore, we examine the specific adaptive mechanisms employed by different groups of aquatic organisms. Fish utilize pathways such as peroxisome proliferator-activated receptor alpha/peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PPAR/PGC-1α) and fatty acid oxidation to optimize energy utilization and improve cold tolerance. Crustaceans rely on crustacean hyperglycemic hormone (CHH) signaling and AMPK pathway activation, while mollusks employ metabolic suppression and glycogen storage to survive cold exposure. Moreover, the regulation of autophagy and apoptosis, mediated by p53 and cyclin-dependent kinase 1 (Cdk1), ensures the survival of healthy cells under prolonged cold stress, with autophagy maintaining energy homeostasis and apoptosis eliminating damaged cells. This review also discusses the role of molecular chaperones like heat shock protein 70 (HSP70) and the ubiquitin-proteasome system (UPS) in protein homeostasis, highlighting their importance to protect cells under cold stress. The combined action of these molecular pathways allows aquatic organisms to cope with and adapt to cold environments, ensuring cellular integrity and enhancing survival. Future research should focus on integrating molecular, physiological, and ecological approaches to better understand cold tolerance mechanisms and improve aquaculture practices under climate change scenarios.

Palatability-by-Design for Oral Drug Products: A Unified Framework for Evaluation and Optimization - Qiaorui Li; Junzhe Xi; Zhenda Liu; Yingying Mu; Lijie Zhao; Lan Shen (AAPS PharmSciTech, 2026)

Mobilizing farmer action for water pollution control: institutional trust and environmental concern in rural China - Lan Mu; Haoying Liu; Ying Li; Qiongyao Wang (Environment, Development and Sustainability, 2026)

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

Corrigendum to “Identification and functional characterization of cGAS and cGAS-like in snakehead Channa argus” [Fish Shellfish Immunol. 165 (2025) 110566] - Hong Qing Zhang; Long Wei Cai; Yu Hang Deng; Meng Xin Yan; Peng Fei Mu; Bo Li; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2026)

Production of carbon nanomaterials from industrial waste salts containing organic pollutants: Carbon quantum dots, graphene, and fullerenes - Pengyao Liu; Lan Li; Lingyun Cao; Xingyu Mu; Meitong Li; Xuening Fei (Journal of Environmental Chemical Engineering, 2026)

Seeds of Transformation: Assessing Farmers' Preferences and Intentions for Improving Agricultural Water‐Saving Irrigation Facilities - Lan Mu; Xuanwen Zeng; Chuanzhen Zhang; Renjie Ma; Ying Li; Qiongyao Wang (Irrigation and Drainage, 2026)
Promoting the enhancement of water‐saving irrigation facilities (WSIFs) within rural communities holds significant practical relevance in addressing agricultural water shortages. Utilizing survey data obtained from 495 farm households within the Wei River Basin in China, this study employs a choice experiment approach that incorporates the extended theory of planned behaviour (TPB) to investigate the willingness of farmers to advance WSIFs. The findings reveal a strong inclination among farmers towards WSIFs progression, with an average willingness‐to‐pay (WTP) of 2877.3 CNY per hectare per year. Significant heterogeneity in farmers' WSIFs preferences is evident, with a notable emphasis on land quality. Conversely, water quality, farmers' income and technical guidance/training have associated WTP values of 370.65, 697.05 and 699.6 CNY/ha/year, respectively. In our further TPB path analysis, factors such as attitudes, subjective norms, perceived behaviour control, knowledge and risk perception emerged as explanatory factors for farmers' intentions to transform their behaviour. Heterogeneity analysis indicates that those predominantly engaged in cash‐crop cultivation, actively utilizing WSIFs and exhibiting high TPB scores tend to display a heightened inclination towards WSIFs and higher WTP. The findings of this study may offer essential insights and feasible guidance for refining policies that promote WSIFs.

Characterization of monoclonal antibody against IgM and phagocytic function of IgM+ B cells in snakehead (Channa argus) - Peng Fei Mu; Zhe Wang; Qi Li; Qiu Hua Li; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2026)

Integration of AD and pyrolysis for char fertilizer: Pyrolysis and nutrient characteristics of biogas residue at different fermentation degrees - Lan Mu; Kongyue Li; Yifan Wang; Biyu Wang; Zhanjun Cheng; Yunan Sun; Yingjin Song; Guanyi Chen (Biomass and Bioenergy, 2026)

Prediction and analysis of polyvinylidene fluoride membrane pyrolysis reaction based on machine learning framework - Hong Su; Yadong Ge; Xiaohua Wang; Lan Mu; Beibei Yan; Guanyi Chen (Journal of Environmental Chemical Engineering, 2025)

Synergistic enhancement of hydrothermal pretreatment and thermal assistance on sludge bio-drying: Microbial stimulation and energy assessment - Lan Mu; Yanhong Zhang; Haixiao Guo; Yunan Sun; Mengying Yun; Jiao Ma (Journal of Environmental Chemical Engineering, 2025)

Flexcube as an alternative aging vessel to the oak barrel: insights into flavor, oxygen, and matrix interactions - Dongsheng Cui; Yongce Huang; Mengqi Ling; Haibin Mu; Weiming Yang; Ying Shi; Changqing Duan; Mengyao Qi; Yibin Lan (Food Research International, 2025)

Comprehensive assessment of full-cycle high-solid anaerobic digestion of straw for methane production update: Focus on performance improvement and circular economy - Yingjin Song; Yinjie Zhong; Yanshan Wang; Lan Mu; Yuxing Luo; Sheng Xu; Huiling Niu; Zhi Wang; Beibei Yan; Guanyi Chen (Environmental Research, 2025)

Integrated machine learning model for prediction of nutrients contents and maturity in rural organic solid wastes aerobic composting - Hao Peng; Lan Mu; Yingjin Song; Hong Su; Yadong Ge; Zhanjun Cheng; Rundong Li; Guanyi Chen (Journal of Environmental Chemical Engineering, 2025)

Preparation of mesoporous carbon/clay composite adsorbent based on the mixed-dimension attapulgite: Dye adsorption, mechanism and molecular dynamics calculations - Shuo Wang; Yuan Zhang; ChengHui Lan; ChaoXi Mu; JianGuo Liu; MengYao Wang; Bin Mu (Journal of Environmental Chemical Engineering, 2025)

Identification and functional characterization of cGAS and cGAS-like in snakehead Channa argus - Hong Qing Zhang; Long Wei Cai; Yu Hang Deng; Meng Xin Yan; Peng Fei Mu; Bo Li; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2025)

Short-chain chlorinated paraffins at environmentally relevant doses disrupt glucose homeostasis and insulin signaling by macrophage-mediated inflammation - Ying-Wen Mu; Wen-Huan Yao; Hui Li; Cui-Li Zhang; Yan-Jing Zhang; Xiu-Ning Zhang; Ge Song; Xiu-Lan Zhao; Tao Zeng (Journal of Hazardous Materials, 2025)

Comparative analysis of rural organic waste treatment: greenhouse gas emissions, economics, and energy flow - Hao Peng; Lan Mu; Yingjin Song; Dan Zeng; Hong Su; Zhanjun Cheng; Rundong Li; Guanyi Chen (Biomass and Bioenergy, 2025)

Implementation or inaction: how governmental multi-interventions catalyze farmers' adoption for climate adaption technology? - Lan Mu; Ying Li; Haoying Liu; Qiongyao Wang (Journal of Cleaner Production, 2025)

Exploring Morphological Indicators for Ramet Age Discrimination of Fargesia nitida Based on Growth Patterns - Xiu-xin Mu; Kai-ming Lei; Hong-ou Sun; Pei-gang Kuang; Yue Zhang; Guo-lan Wang; Tao Zeng (Journal of Plant Growth Regulation, 2025)

Corrigendum to “Changes of unique flavor substances and metabolic pathway brought by Lacticaseibacillus rhamnosus WH. FH-19 fermented milk during fermentation and storage stage: HS-SPME-GC-MS and HPLC-MS-based analysis” [Food Bioscience 65 (2025) 1–11/105974] - Lu Feng; Jingxia Yang; Liping Sun; Xiaoyan Zhu; Wei Lan; Guangqing Mu; Xuemei Zhu (Food Bioscience, 2025)

Deciphering the Synergies between Carbon Tax and Water Conservation: A Water Footprint Analysis - Lan Mu; Renjie Ma; Chuanzhen Zhang; Xuanwen Zeng; Qi Zhou (Environmental Management, 2025)

Anaerobic co-digestion of antibiotic fermentation residues and corn stalks for biogas production and elimination of antibiotic resistance genes - Beibei Yan; Xin Chen; Zhi Wang; Jian Li; Tangwei Li; Lan Mu; Guanyi Chen (Fuel, 2025)

Changes of unique flavor substances and metabolic pathway brought by Lacticaseibacillus rhamnosus WH. FH-19 fermented milk during fermentation and storage stage: HS-SPME-GC-MS and HPLC-MS-based analysis - Lu Feng; Jingxia Yang; Liping Sun; Xiaoyan Zhu; Wei Lan; Guangqing Mu; Xuemei Zhu (Food Bioscience, 2025)

The influence of polyphenols on the hydrolysis and formation of volatile esters in wines during aging: An insight of kinetic equilibrium reaction - Mengqi Ling; Dongsheng Cui; Baoqing Zhu; Demei Li; Haibin Mu; Jin Li; Ying Shi; Changqing Duan; Yibin Lan (Food Chemistry, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Diatom assemblages indicated ecological shifts over the past two centuries in Bosten Lake, northwest China: Natural and anthropogenic forcings - Muhammad Farqan; Lixiong Xiang; Lan Jiang; Wenjia Wang; Min Zheng; Xiaoyan Mu; Xin Liu; Xueqing Song; Zezhou Zhu; Ramamoorthy Ayyamperumal; Xiaozhong Huang (Quaternary International, 2025)

Protonated polyethyleneimine enables synchronous crosslinking of polyimide nanofiltration membranes for dye desalination - Qing Fang; Sudan Lan; Xiuxiu Mu; Yanping Zhang; Ya Li; Yajuan Wang; Lihui Yao; Yuyun Chen; Dan Qiu; Linghui Wang (Desalination, 2024)

A green and sustainable technology for the development of artificial protein fibers from sorghum distillers grains for industrialization - Yuanyi Shao; Bingnan Mu; Lan Xu; Yiqi Yang (Chemical Engineering Journal, 2024)

8-Br-cGMP suppresses tumor progression through EGFR/PLC γ1 pathway in epithelial ovarian cancer - Min Wu; Chunyan Mu; Huiwen Yang; Yue Wang; Ping Ma; Shibao Li; Zhongcheng Wang; Ting Lan (Molecular Biology Reports, 2024)

Western Mongolian Plateau exhibits increasing Holocene temperature - Chong Huang; Xiaozhong Huang; Jinbao Li; Ling Wang; Lan Jiang; Lixiong Xiang; Jun Zhang; Yu Hu; Xiaoyan Mu; Min Zheng; Xiuxiu Ren; Tao Wang; et al. (Global and Planetary Change, 2024)

Involvement of Hg-bearing methane seeps in forming Ediacaran cap carbonate in South China - Xiaodie Mu; Xiangdong Wang; Zhongwu Lan; He Zhao; Zhong-Qiang Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Effects of a Chinese herbal medicine mixture on growth performance, immune response, and gene expression in Chinese soft-shelled turtles (Pelodiscus sinensis) - Mengyan Lan; Yaguang Wang; Yuqi Mu; Yali Li; Zhao Zhang; Yueqiang Guan (Animal Feed Science and Technology, 2024)

Effects of straw management and N levels on gross nitrogen transformations in fluvo-aquic soil of the North China Plain - Guocui Ren; Xianfeng Zhang; Jinbo Zhang; Lan Mu; Xiuli Xin; Yiming Yun; Anning Zhu; Shuchun Ge (Science of The Total Environment, 2024)

Turning trash into treasure: Integrating waste MXene sediment with bagasse into photothermal composite aerogel for efficient solar-driven interfacial evaporation - Xiaoyan Lu; Chunxia Mu; Liqin Nong; Changlan Lan; Zhangfa Tong; Kelei Huang (Chemical Engineering Journal, 2024)

Neuroprotective Effects of Metformin on Cerebral Ischemia-Reperfusion Injury: Modulation of JNK and p38 MAP Kinase Signaling Pathways - Shicun Zhang; Wei Zou; Yan Leng; Zhuang Mu; Lan Zhan (Cell Biochemistry and Biophysics, 2024)

Subnanometric Pt-Ga alloy clusters confined within Silicalite-1 zeolite for n-hexane dehydrogenation - Mu He; Guanyu Qie; Zhangfa Tong; Yueqin Song; Rizwan Muhammad; Xiaolong Zhou; Jin An Wang; Ping Lan (Fuel, 2024)

Missing microbes in infants and children in the COVID-19 pandemic: a study of 1,126 participants in Beijing, China - Jiejing Wang; Yuejuan Li; Yu Mu; Kefei Huang; Danyi Li; Canhui Lan; Yutao Cui; Jun Wang (Science China Life Sciences, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Pretreatment with rumen fluid improves methane production in the anaerobic digestion of corn straw - Fenglian Xu; Lan Mu; Yifan Wang; Hao Peng; Junyu Tao; Guanyi Chen (Fuel, 2024)

Graphene oxide quantum dots (GOQDs) induce behavioral disorders via the disturbance of kynurenine pathway in zebrafish larvae - Shun Deng; Enming Zhang; Yunyang Zhao; Hao Guo; Lan Luo; Song Yi; Bingxin Zheng; Xiaoyuan Mu; Kezhu Yuan; Xuangen Deng; Haibo Rong; Yanbo Ma; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

A hybrid approach of anaerobic digestion model no. 1 and machine learning to model and optimize continuous anaerobic digestion processes - Yadong Ge; Junyu Tao; Zhi Wang; Lan Mu; Wei Guo; Zhanjun Cheng; Beibei Yan; Yan Shi; Hong Su; Guanyi Chen (Biomass and Bioenergy, 2024)

Enhancement of methane production from anaerobic digestion of Erigeron canadensis via O2-nanobubble water supplementation - Legeng Pei; Yingjin Song; Guanyi Chen; Lan Mu; Beibei Yan; Teng Zhou (Chemosphere, 2024)

Preparation of iron oxide-modified digestate biochar and effect on anaerobic digestion of kitchen waste - Yifan Wang; Lan Mu; Chen Chen; Fenglian Xu; Hao Peng; Yingjin Song; Guanyi Chen (Bioresource Technology, 2024)

Acetylenic spiroketal enol ethers from Artemisia rupestris and their synergistic antibacterial effects on methicillin-resistant Staphylococcus aureus - Chuan-Yun Xiao; Jiang-Er Lan; Xiao Liu; Zhong-Lin Sun; Xiao-Jin Li; Yi-Han Yin; Simon Gibbons; Qing Mu (Natural Product Research, 2024)

Paleoenvironmental evolution preceding the end-Permian mass extinction in the Lower Yangtze region (South China) and its controls on extreme enrichment of organic matter - Lan Mu; Bolin Zhang; Jian Cao; Suping Yao; Wenxuan Hu; Xianguo Lang; Fengcun Xing; Zhiwei Liao; Yuping Li; Jie Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Effect of heterogeneous fenton-like pretreatment on semi-permeable membrane-covered co-composting: Humification and microbial community succession - Yingjin Song; Yu Hou; Lan Mu; Guanyi Chen; Yamei Zeng; Beibei Yan (Bioresource Technology, 2024)

The Impacts of Agricultural Water Pricing on Sustainable Agricultural Production - Lan Mu; Yuan Wang; Binrui Xue (Water Resources Management, 2024)

GPX2 acts as an oncogene and cudraflavone C has an anti-tumor effect by suppressing GPX2-dependent Wnt/β-catenin pathway in colorectal cancer cells - Zhuo Wu; Su Zhou; Dan Liang; Lan Mu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Atomic force microscopy-based nanoscale infrared techniques for liquid environments - Jian Li; Jing Liang; Mu-Hao Lan; Xing-Hua Xia (Science Bulletin, 2024)

Comprehensive understanding on sources of high levels of fine particulate nitro-aromatic compounds at a coastal rural area in northern China - Yueru Jiang; Xinfeng Wang; Min Li; Yiheng Liang; Zhiyi Liu; Jing Chen; Tianyi Guan; Jiangshan Mu; Yujiao Zhu; He Meng; Yang Zhou; Lan Yao; et al. (Journal of Environmental Sciences, 2024)

Effects of florfenicol on the antioxidant and immune systems of Chinese soft-shelled turtle (Pelodiscus sinensis) - Yuqi Mu; Mengyan Lan; Yali Li; Zhao Zhang; Yueqiang Guan (Fish & Shellfish Immunology, 2023)

The Permian Chert Event in South China: New geochemical constraints and global implications - Bolin Zhang; Jian Cao; Lan Mu; Suping Yao; Wenxuan Hu; Hu Huang; Xianguo Lang; Zhiwei Liao (Earth-Science Reviews, 2023)

Exploring the contribution of the river chief system on controlling industrial water pollution under quasi-natural experimental conditions - Lan Mu; Zongjia Tan; Chunxia Luo; Na Qiao (Environmental Science and Pollution Research, 2023)

Size-controllable Rh2P nanoparticles on reduced graphene oxide toward highly hydrogen production - Hongqiang Xin; Lan Sun; Yiwei Zhao; Yuanjiang Lv; Qiaomei Luo; Shengwu Guo; Danyang Li; Ce Mu; Bo Huang; Fei Ma (Chemical Engineering Journal, 2023)

The potential health risks of short-chain chlorinated paraffin: A mini-review from a toxicological perspective - Ying-Wen Mu; Dong Cheng; Cui-Li Zhang; Xiu-Lan Zhao; Tao Zeng (Science of The Total Environment, 2023)

Crowdsourced text analysis to characterize the U.S. National Parks based on cultural ecosystem services - Inhye Kong; Fausto O. Sarmiento; Lan Mu (Landscape and Urban Planning, 2023)

Investigation on the formation mechanism of main products from TBBPA pyrolysis using DFT method - Xin Mu; Yao Wang; Jinbao Huang; Lin Lan; Hong Wang; Weiwei Xu; Xinsheng Li (Chemosphere, 2023)

Exploring preference and willingness for rural water pollution control: A choice experiment approach incorporating extended theory of planned behaviour - Lan Mu; Muge Mou; Heyan Tang; Shengrong Gao (Journal of Environmental Management, 2023)

Rational fabrication of completely amorphous chitosan-formyl-sucrose sorbents with excellent durability and regenerability for high-throughput dye removal - Bingnan Mu; Lan Xu; Yiqi Yang (Chemical Engineering Journal, 2023)

Comparative analyses of five complete chloroplast genomes from the endemic genus Cremanthodium (Asteraceae) in Himalayan and adjacent areas - Weihong Zhong; Xiaolang Du; Xiaoyun Wang; Lan Cao; Zejing Mu; Guoyue Zhong (Physiology and Molecular Biology of Plants, 2023)

Recent advancements in strategies to improve anaerobic digestion of perennial energy grasses for enhanced methane production - Yingjin Song; Legeng Pei; Guanyi Chen; Lan Mu; Beibei Yan; Hongji Li; Teng Zhou (Science of The Total Environment, 2023)

An assessment of rainfall kinetic energy functional relationships with GPM DPR - Jayalakshmi Janapati; Balaji Kumar Seela; Pay-Liam Lin; Chen-Hau Lan; Chuan-Chi Tu; Utpal Kumar; Mu-Qun Huang (Journal of Hydrology, 2023)

Modification of anaerobic digestion model No.1 with Machine learning models towards applicable and accurate simulation of biomass anaerobic digestion - Yadong Ge; Junyu Tao; Zhi Wang; Chao Chen; Lan Mu; Haihua Ruan; Yakelin Rodríguez Yon; Hong Su; Beibei Yan; Guanyi Chen (Chemical Engineering Journal, 2023)

Simulation of integrated anaerobic digestion-gasification systems using machine learning models - Yadong Ge; Junyu Tao; Zhi Wang; Chao Chen; Rui Liang; Lan Mu; Haihua Ruan; Yakelin Rodríguez Yon; Beibei Yan; Guanyi Chen (Bioresource Technology, 2023)

Theoretical study on pyrolysis mechanism of decabromodiphenyl ether (BDE-209) using DFT method - Yao Wang; Jinbao Huang; Hong Wang; Lin Lan; Xin Mu; Weiwei Xu; Shanjin Lv; Xinsheng Li (Chemosphere, 2023)

Attitudes and opportunities: comparing climate change adaptation intentions and decisions of agricultural producers in Shaanxi, China, and British Columbia, Canada - Lan Mu; Johannus Janmaat; Joanne Taylor; Lauren Arnold (Mitigation and Adaptation Strategies for Global Change, 2023)

Co-composting of cattle manure and wheat straw covered with a semipermeable membrane: organic matter humification and bacterial community succession - Yingjin Song; Ruiyi Li; Yuxin Wang; Yu Hou; Guanyi Chen; Beibei Yan; Zhanjun Cheng; Lan Mu (Environmental Science and Pollution Research, 2022)

Evolution mechanism and deformation stability analysis of rock slope block toppling for early warnings - Jian-qiao Mu; Tian-tao Li; Xiang-jun Pei; Run-qiu Huang; Fu-an Lan; Xue-qing Zou (Natural Hazards, 2022)

The differential impact of air pollutants on acute urticaria and chronic urticaria: a time series analysis - Jiawei Li; Guoqiang Song; Zhenzhen Mu; Xiaoou Lan; Fan Yang; Lin Li; Xiuping Han (Environmental Science and Pollution Research, 2022)

Quick mapping and characterization of a co-located kernel length and thousand-kernel weight-related QTL in wheat - Xiangru Qu; Cong Li; Hang Liu; Jiajun Liu; Wei Luo; Qiang Xu; Huaping Tang; Yang Mu; Mei Deng; Zhien Pu; Jun Ma; Qiantao Jiang; et al. (Theoretical and Applied Genetics, 2022)

Enantioselective hydrolysis and photolysis of mandipropamid in different aquatic environments — evaluation of influencing factors - Jianmin Li; Jiahua Han; Tingting Lan; Shiyin Mu; Deyu Hu; Kankan Zhang (Environmental Science and Pollution Research, 2022)

Linkages among the functional traits, insect visitation rate and seed set of Gentiana taxa on the Tibetan Plateau - Wen-fei Dai; Rui Gao; Meng-ying He; Yu-lian Yang; Fang-lan Li; Jun-peng Mu (Journal of Mountain Science, 2022)

Characterization and fine mapping of a lesion mimic mutant (Lm5) with enhanced stripe rust and powdery mildew resistance in bread wheat (Triticum aestivum L.) - Cong Li; Hang Liu; Jian Wang; Qi Pan; Yue Wang; Kunyan Wu; Peiying Jia; Yang Mu; Huaping Tang; Qiang Xu; Qiantao Jiang; Yaxi Liu; et al. (Theoretical and Applied Genetics, 2022)

Flavonoids from Artemisia rupestris and their synergistic antibacterial effects on drug-resistant Staphylococcus aureus - Jiang-Er Lan; Xiao-Jin Li; Xiao-Feng Zhu; Zhong-Lin Sun; Jian-Ming He; Mire Zloh; Simon Gibbons; Qing Mu (Natural Product Research, 2021)

Enhancing capacity building to climate adaptation and water conservation among Chinese young people - Lan Mu; Yuhong Liu; Chencheng Wang; Xiaojuan Qu; Yaochuang Yu (Environmental Science and Pollution Research, 2021)

QTL mapping and validation of bread wheat flag leaf morphology across multiple environments in different genetic backgrounds - Yang Tu; Hang Liu; Jiajun Liu; Huaping Tang; Yang Mu; Mei Deng; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Jirui Wang; Pengfei Qi; Zhien Pu; et al. (Theoretical and Applied Genetics, 2021)

A novel, validated, and plant height-independent QTL for spike extension length is associated with yield-related traits in wheat - Cong Li; Huaping Tang; Wei Luo; Xuemei Zhang; Yang Mu; Mei Deng; Yaxi Liu; Qiantao Jiang; Guoyue Chen; Jirui Wang; Pengfei Qi; Zhien Pu; et al. (Theoretical and Applied Genetics, 2020)

A novel, major, and validated QTL for the effective tiller number located on chromosome arm 1BL in bread wheat - Jiajun Liu; Huaping Tang; Xiangru Qu; Hang Liu; Cong Li; Yang Tu; Shuiqing Li; Ahsan Habib; Yang Mu; Shoufeng Dai; Mei Deng; Qiantao Jiang; et al. (Plant Molecular Biology, 2020)

Effects of the 1BL/1RS translocation on 24 traits in a recombinant inbred line population - Hang Liu; Huaping Tang; Puyang Ding; Yang Mu; Ahsan Habib; Yaxi Liu; Qiantao Jiang; Guoyue Chen; Houyang Kang; Yuming Wei; Youliang Zheng; Xiujin Lan; et al. (Cereal Research Communications, 2020)

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Identification and characterization of mRNAs and lncRNAs of a barley shrunken endosperm mutant using RNA-seq - Yaya Zou; Huaping Tang; Ting Li; Min Sun; Xiangru Qu; Jieguang Zhou; Congcong Yang; Yang Mu; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Guangdeng Chen; et al. (Genetica, 2020)

Effect of using banana by-products and other agricultural residues for beef cattle in southern China - Zhulin Xue; Lan Mu; Ming Cai; Yingjun Zhang; Metha Wanapat; Bizhi Huang (Tropical Animal Health and Production, 2020)

Assessment of ramie leaf (Boehmeria nivea L. gaud) as an animal feed supplement in P.R. China - Lan Mu; Ming Cai; Zongli Wang; Jianyong Liu; Tianliang Liu; Metha Wanapat; Bizhi Huang (Tropical Animal Health and Production, 2020)

Correction to: Identification and validation of a major and stably expressed QTL for spikelet number per spike in bread wheat - Jian Ma; Puyang Ding; Jiajun Liu; Ting Li; Yaya Zou; Ahsan Habib; Yang Mu; Huaping Tang; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Jirui Wang; et al. (Theoretical and Applied Genetics, 2020)

Flag leaf size and posture of bread wheat: genetic dissection, QTL validation and their relationships with yield-related traits - Jian Ma; Yang Tu; Jing Zhu; Wei Luo; Hang Liu; Cong Li; Shuiqin Li; Jiajun Liu; Puyang Ding; Ahsan Habib; Yang Mu; Huaping Tang; et al. (Theoretical and Applied Genetics, 2020)

Identification and validation of a major and stably expressed QTL for spikelet number per spike in bread wheat - Jian Ma; Puyang Ding; Jiajun Liu; Ting Li; Yaya Zou; Ahsan Habib; Yang Mu; Huaping Tang; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Jirui Wang; et al. (Theoretical and Applied Genetics, 2019)

Association between occupational exposure to trichloroethylene and serum levels of microRNAs: a cross-sectional molecular epidemiology study in China - Kyoung-Mu Lee; Bryan A. Bassig; Luoping Zhang; Roel C. Vermeulen; Wei Hu; Jason Y. Y. Wong; Chuangyi Qiu; Cuiju Wen; Yongshun Huang; Mark P. Purdue; Bu-Tian Ji; Laiyu Li; et al. (International Archives of Occupational and Environmental Health, 2019)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

Resina draconis inhibits the endoplasmic-reticulum-induced apoptosis of myocardial cells via regulating miR-423-3p/ERK signaling pathway in a tree shrew myocardial ischemia–reperfusion model - Tian-Rui Yang; Tong Zhang; Ning-Hui Mu; Li-Bo Ruan; Jin-Lan Duan; Rong-Ping Zhang; Yun-Bo Miao (Journal of Biosciences, 2019)

Identification and validation of a novel major QTL for all-stage stripe rust resistance on 1BL in the winter wheat line 20828 - Jian Ma; Nana Qin; Ben Cai; Guoyue Chen; Puyang Ding; Han Zhang; Congcong Yang; Lin Huang; Yang Mu; Huaping Tang; Yaxi Liu; Jirui Wang; et al. (Theoretical and Applied Genetics, 2019)

Four new phenolic constituents from the rhizomes of Gastrodia elata Blume - Zhi-Wei Wang; Yun Li; Da-Hui Liu; Yan Mu; Hong-Jing Dong; Hong-Lei Zhou; Lan-Ping Guo; Xiao Wang (Natural Product Research, 2019)

A 55 K SNP array-based genetic map and its utilization in QTL mapping for productive tiller number in common wheat - Jiajun Liu; Wei Luo; Nana Qin; Puyang Ding; Han Zhang; Congcong Yang; Yang Mu; Huaping Tang; Yaxi Liu; Wei Li; Qiantao Jiang; Guoyue Chen; et al. (Theoretical and Applied Genetics, 2018)

Identification and Field Evaluation of the Sex Pheromone of Orthaga achatina (Lepidoptera: Pyralidae) - Qi Yan; Hai-Dong Li; Yan Chen; Zhan-Feng Ye; Xi-Yu You; Jun Zhou; Lan-Fang Mu; Shi-Jing Liu; Xiang-Bo Kong; Sajjad Ali Khuhro; Shuang-Lin Dong (Journal of Chemical Ecology, 2018)

Ionizing radiation exposure: hazards, prevention, and biomarker screening - Hongxiang Mu; Jing Sun; Linwei Li; Jie Yin; Nan Hu; Weichao Zhao; Dexin Ding; Lan Yi (Environmental Science and Pollution Research, 2018)

Efficient Using Durian Shell Hydrolysate as Low-Cost Substrate for Bacterial Cellulose Production by Gluconacetobacter xylinus - Mu-Tan Luo; Cheng Zhao; Chao Huang; Xue-Fang Chen; Qian-Lin Huang; Gao-Xiang Qi; Lan-Lan Tian; Lian Xiong; Hai-Long Li; Xin-De Chen (Indian Journal of Microbiology, 2017)

The Role of Reelin Signaling in Alzheimer’s Disease - Nan-Nan Yu; Meng-Shan Tan; Jin-Tai Yu; An-Mu Xie; Lan Tan (Molecular Neurobiology, 2016)

Characterization of the Aggregation-Induced Enhanced Emission of N,N′-bis(4-methoxysalicylide)benzene-1,4-diamine - Fuyong Wu; Guangjun Xu; Xi Zeng; Lan Mu; Carl Redshaw; Gang Wei (Journal of Fluorescence, 2015)

A novel MVK missense mutation in one Chinese family with disseminated superficial actinic porokeratosis - Wen-sheng Lu; Xiao-dong Zheng; Xiu-hua Yao; Lan-fang Zhang; Mu-Qiu Wang; Fa-Xing Jiang; Si-Ping Zhang; Bai Hu (Molecular Biology Reports, 2014)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

A fully human CD19/CD3 bi-specific antibody triggers potent and specific cytotoxicity by unstimulated T lymphocytes against non-Hodgkin’s lymphoma - Yan Zhou; Lan-tu Gou; Bo Mu; Wei-chan Liao; Jing He; Cong Ma; Yu-qin Yao; Jin-liang Yang (Biotechnology Letters, 2012)

Clinical significance of peritumoral lymphatic vessel density and lymphatic vessel invasion detected by D2-40 immunostaining in FIGO Ib1-IIa squamous cell cervical cancer - Ying Xiong; Li-Ping Cao; Hui-Lan Rao; Mu-Yan Cai; Li-Zhi Liang; Ji-Hong Liu (Cell and Tissue Research, 2012)

Optimisation of preparation conditions and properties of phytosterol liposome-encapsulating nattokinase - Xu-Yan Dong; Fan-Pi Kong; Gang-You Yuan; Fang Wei; Mu-Lan Jiang; Guang-Ming Li; Zhan Wang; Yuan-Di Zhao; Hong Chen (Natural Product Research, 2012)

Large-scale sequencing of normalized full-length cDNA library of soybean seed at different developmental stages and analysis of the gene expression profiles based on ESTs - Ai-Hua Sha; Chen Li; Xiao-Hong Yan; Zhi-Hui Shan; Xin-An Zhou; Mu-Lan Jiang; Han Mao; Bo Chen; Xia Wan; Wen-Hui Wei (Molecular Biology Reports, 2012)

Positive allelopathic stimulation and underlying molecular mechanism of achyranthe under continuous monoculture - Zhen-Fang Li; Zi-Guan Zhang; Dong-Feng Xie; Lin-Quan Dai; Lan-Fang Zhu; Ji Li; Zong-Quan Liu; Yan-Qiu Yang; Lin-Kun Wu; Mu-Ji Huang; Zhong-Yi Zhang; Wen-Xiong Lin (Acta Physiologiae Plantarum, 2011)

Polyclonal rabbit anti-murine plasmacytoma cell globulins induce myeloma cells apoptosis and inhibit tumour growth in mice - Bo Mu; Jin-liang Yang; Lan-tu Gou; Yu-qin Yao; Yan Zhou; Zhi-hui Cheng; Hua-shan Shi; Zhi-yong Li; Yuan Wen; Fei Leng; Feng-yu Cui; Tian-tai Ma; et al. (Apoptosis, 2011)

Reproductive failure in wild boars associated to porcine parvovirus infection and in vivo and in vitro characterization of the causal isolate - Chao-fan Zhang; Cui-Ping Song; Chang-mu Chen; Shang-jin Cui; Lan-fei Miao (Tropical Animal Health and Production, 2010)

The effective expression of xylanase gene in Candida utilis by 18S rDNA targeted homologous recombination in pGLR9K - Wang Wei; Yang Hong-Lan; Bao HuiFang; Zhang Daoyuan; Shan Qi-mu-ge; Andrew J. Wood (Molecular Biology Reports, 2010)

Recombinant ORF66 and ORFK12 antigens for the detection of human herpesvirus 8 antibodies in HIV-positive and -negative patients - Tsuey-Ching Yang; Chun-Pin Chang; Yu-Ching Lan; Chao-Li Liu; Mu-Chin Shih; Fang-Yang Wu; Cheng-Wen Lin (Biotechnology Letters, 2009)

Efficient organogenesis and plantlet regeneration in the timber species Cunninghamia lanceolata (Lamb.) Hook - Mu-lan Zhu; Ji Wang; Yang Yu; Sheng-jun Liu; Zhi-ming Wei (In Vitro Cellular & Developmental Biology - Plant, 2007)

One-carbon metabolism gene polymorphisms and risk of non-Hodgkin lymphoma in Australia - Kyoung-Mu Lee; Qing Lan; Anne Kricker; Mark P. Purdue; Andrew E. Grulich; Claire M. Vajdic; Jennifer Turner; Denise Whitby; Daehee Kang; Stephen Chanock; Nathaniel Rothman; Bruce K. Armstrong (Human Genetics, 2007)

Release and extracellular metabolism of ATP by ecto-nucleotidase eNTPDase 1–2 in hypothalamic and pituitary cells - Mu-Lan He; Arturo E. Gonzalez-Iglesias; Melanija Tomic; Stanko S. Stojilkovic (Purinergic Signalling, 2005)

A spatial cluster method supported by GIS for urban-suburban-rural classification - De-min Zhou; Jian-chun Xu; John Radke; Lan Mu (Chinese Geographical Science, 2004)

Isothermal and Nonisothermal Decomposition of Thymopentin and Its Analogs in Aqueous Solution - Mu-Lan Lee; Salomon Stavchansky (Pharmaceutical Research, 1998)